Readmission and mortality one year after acute hospitalization in older patients with explained and unexplained anemia - a prospective observational cohort study. Issue 1 (December 2016) - Abrahamsen, Jenny; Monsen, Anne-Lise; Landi, Francesco; Haugland, Cathrine; Nilsen, Roy; Ranhoff, Anette
Abstract Background Few studies have examined whether specific subtypes of anemia in older persons are more related to adverse outcomes such as hospital readmissions and death after acute hospitalization and post-acute care. Methods An observational prospective cohort study was conducted between 2011 and 2014. A total of 884 community-dwelling patients, ≥70 years of age were transferred from acute medical and orthopaedic hospital departments to a skilled nursing home where they were examined by comprehensive geriatric assessment and had laboratory tests taken for the investigation of anemia. They were divided into three major groups and compared; 1) no anemia (reference group), 2) explained anemia (renal insufficiency, iron deficiency, vitaminB12/folate deficiency or multifactorial anemia) and 3) unexplained anemia. The groups were compared, and association of anemia with hospital readmission and death was estimated by logistic regression analyses. Results Compared to the patients with unexplained anemia (n =135), patients with explained anemia (n =275) had more often died (22 % vs. 14 %, p =0.05) and had more frequenlty been readmitted to hospital (39 % vs. 27 %, p =0.03). Compared to the patients without anemia (n =474), the patients with explained anemia had increased odds of hospital readmissions (OR = 1.54 (95 % CI: 1.05–2.25), p =0.03), while patients with unexplained anemia, (n =135), had neither increased odds of hospital readmissions, (OR=0.83, 95 % CI: 0.51–1.34, p =0.44) nor death (OR = 0.74, 95 % CI: 0.41–1.31, p =0.30), in adjusted regression analysis. Conclusion Since no increased risk of hospital readmissions or death was seen in older patients with unexplained anemia in the first year after acute hospitalization, no further invasive investigations might be necessary to investigate the cause of anemia in these patients. A close clinical follow up might be the best way to care for older patients with a mild and unexplained anemia.